Antimicrobial resistance of Escherichia coli strains causing community-acquired urinary tract infections among insured and uninsured populations in a large urban center - Moreira Junior, Edson Duarte (2006)
Fundação Oswaldo Cruz. Centro de Pesquisas Gonçalo Moniz. Salvador, BA, Brasil / Associação Obras Sociais Irmã Dulce. Núcleo de Apoio à Pesquisa. Salvador, BA, Brasil / Hospital São Rafael. Salvador, BA, Brasil